THE SUCCESS FACTORS FOR PROMOTING SAVINGS DISCIPLINE WITH THE NATIONAL SAVINGS FUND IN NAKHON SAWAN PROVINCE - Phettun, Saran; Mhuentoei, Tanongsak (Journal of MCU Nakhondhat, 2024)
This research aimed to study the level of success in promoting savings discipline with the National Savings Fund (NSF) in Nakhon Sawan Province and to analyze factors affecting success in promoting savings discipline with the NSF in Nakhon Sawan Province. The research population consisted of 1,600 project officers. The sample size of 320 people was determined using Taro Yamane’s formula. Stratified random sampling was conducted based on the project operator groups, followed by simple random sampling according to the specified proportion. Quality-validated questionnaires were utilized to gather data in November 2023. The data were analyzed using frequency distribution, percentage, mean, standard deviation and multiple regressions. The results found that the level of success, overall, in promoting savings discipline with the NSF in Nakhon Sawan Province had an average score at a high level ( = 3.93, S.D. = 0.49). This success consisted of the achievements in the number of members who participated in the project to promote savings discipline with the NSF in Nakhon Sawan Province per goal reaching the highest level ( = 4.24, S.D. = 0.53) and the success in promoting the continuous savings discipline of participating members being successful at a high level ( = 3.62, S.D. = 0.49) respectively. The hypothesis testing demonstrated that all six factors tested positively affected the project’s success in promoting savings discipline with the NSF in Nakhon Sawan Province at a statistically significant level of 0.05. These factors include the cooperation or response of policy implementers factor (R2 = 0.613), the characteristics of implementing policy agencies factor (R2 = .581), the economic, social, and political resource conditions factor (R2 = .578), the resources of policy factor (R2 = .574), the interagency communication factor (R2 = .562), and the policy standards and objectives factor (R2 = .491).